2022
DOI: 10.1136/neurintsurg-2021-018428
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of patients with mild pre-stroke morbidity following endovascular treatment: a HERMES substudy

Abstract: BackgroundAnalyses of the effect of pre-stroke functional levels on the outcome of endovascular therapy (EVT) have focused on the course of patients with moderate to substantial pre-stroke disability. The effect of complete freedom from pre-existing disability (modified Rankin Scale (mRS) 0) versus predominantly mild pre-existing disability/symptoms (mRS 1–2) has not been well delineated.MethodsThe HERMES meta-analysis pooled data from seven randomized trials that tested the efficacy of EVT. We tested for a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Third, we could not draw valid conclusions about patients with a prestroke mRS of 5 because EVT was very uncommon in this population. Four, one ( 25 ) of the three studies that compared the outcomes between EVT and SMT involved some patients with mRS 1, also limiting the validity of our findings.…”
Section: Discussionmentioning
confidence: 71%
“…Third, we could not draw valid conclusions about patients with a prestroke mRS of 5 because EVT was very uncommon in this population. Four, one ( 25 ) of the three studies that compared the outcomes between EVT and SMT involved some patients with mRS 1, also limiting the validity of our findings.…”
Section: Discussionmentioning
confidence: 71%
“…36,37 Indeed, a post hoc analysis of the HERMES collaboration showed that clinical outcome at 3 months is worse in patients with mild preexisting disability (mRS score 1–2), but this held true both for the control and EVT arms. 16 Furthermore, there was no evidence of treatment effect modification of EVT by prestroke mRS, suggesting that the effect of EVT is similar in patients with and without mild preexisting symptoms/disability. Although the former may be at a slightly higher risk of death compared with the latter, they are not more likely to accumulate additional disability over and beyond their preexisting deficits compared to those patients without preexisting symptoms/disability.…”
Section: Discussionmentioning
confidence: 90%
“…HERMES included 199 patients with prestroke mRS score 1 or 2; 98 in the EVT arm and 101 in the best medical management arm. 16…”
Section: Methodsmentioning
confidence: 99%
“…While the mRS is a validated measure to assess poststroke neurological and functional outcomes, 14 whether it is an appropriate tool to quantify non-neurological disability prior to stroke onset is unclear. Past studies have demonstrated that prestroke mRS is a negative prognostic factor for post-EVT outcomes, [15][16][17] however, no study to date has investigated whether these associations apply to both neurological and non-neurological causes of higher prestroke mRS. There is currently little guidance on how to assess non-neurological disability during acute triage, and using prestroke mRS to quantify disability from osteoarthritis and other musculoskeletal diseases has not been validated.…”
Section: Discussionmentioning
confidence: 99%